Drypoint printmaking: alternative material and technique for Open and Distance Learning (ODL) / Noor A’yunni Muhamad … [et al.] - Muhamad, Noor A’yunni; Ramli, Ishak; Tahir, Azian; Desa, Noor Enfendi; Mohd Aripin, Nur Adibah Nadiah; Arshad, Mohd Fawazie (Faculty of Art and Design, 2022)
Drypoint refers to an intaglio sub-section printmaking technique (non-acid technique) of which a rough needle is used to make scratches across the plate (metal or copper plate) surfaces. Since March 2020, the education system is one of the sectors which has been affected by the pandemic and the process of teaching and learning was determined to be delivered through Open Distance Learning (ODL). Since drypoint printmaking is a part of the Fine Art education syllabus, this research aims to explore an alternative in drypoint printmaking, especially in the exploration of material and techniques without compromising the aesthetic and rules in drypoint. The method that will be used in this research is qualitative research through exploratory action research approach. This method is significant in terms of exploring other alternatives in substituting the role of equipment such as etching press and other possible materials. In this research, the comparative method from the aspect of material and technique will be used since it involves comparing circumstances, classes, cultures, or anything that are similar and yet different in comprehensible ways. The outcome from this study will produce the result of whether the alternative method and technique can achieve the same kind of quality as the common practice of the drypoint printmaking technique. Based on the findings, the researcher will develop a formal guideline for educators and art practitioners to expand this alternative technique as an approach in achieving the best quality of drypoint printmaking artworks without having to worry about lack of experience in an art studio environment or complete equipment. In the future, there should be more exploration, especially on the alternative material and technique in Drypoint printmaking.